Penerapan Media Bergambar Dalam Meningkatkan Pembelajaran Kosa Kata di MIN 1 Probolinggo - Isnol Khotimah; Moh. Ulum; Firda Aprilia Yutami (Universitas Yudharta Pasuruan, 2021)
This study aims to fully explain the application of pictorial media in improving Arabic vocabulary. The method used in this research is descriptive qualitative which aims to explain the application of pictorial media in improving Arabic vocabulary learning. So that students can develop vocabulary well so that students can improve language skills, namely: listening, speaking, reading, and also writing. The results of the research we obtained, show that firstly, with the implementation of pictorial media in increasing Arabic vocabulary, students prefer pictures and writing that are more interesting, secondly, the benefits of pictorial media for learning are clearer and more interesting, the third is the steps for using pictorial media. in front of the class. Fourth, the strengths and weaknesses of students in memorizing vocabulary. The class atmosphere is lively, and the five problems and solutions in the application of illustrated media are Arabic learning materials which are quite difficult, so the solution to learning Arabic with pictorial media at MIN 1 Probolinggo will look effective and efficient if it is done with pictorial visual media, the use of pictorial media is the achievement of a more interesting learning climate.